Menopausal Transition: Prospective Study of Estrogen Status, Circulating MicroRNAs, and Biomarkers of Bone Metabolism - Jiri Baloun; Jiri Baloun; Aneta Pekacova; Aneta Pekacova; Laszlo Wenchich; Hana Hruskova; Hana Hruskova; Ladislav Senolt; Ladislav Senolt; Xiao Svec; Karel Pavelka; Karel Pavelka; et al. (Frontiers in Endocrinology, 2022)
ObjectiveOsteoporosis is associated with an impaired balance between bone resorption and formation, which in turn leads to bone loss and fractures. Many recent studies have underlined the regulatory role of microRNAs (miRNAs) in bone remodeling processes and their potential as biomarkers of osteoporosis. The purpose of this study was to prospectively examine the association of circulating miRNAs and bone biomarkers with estrogen status in women before and after oophorectomy, as well as in oophorectomized women on estrogen therapy.MethodsIn this prospective study, we included 11 women before oophorectomy and hysterectomy and at 201 ± 24 days after the surgery. Another 11 women were evaluated 508 ± 127 days after oophorectomy and hysterectomy and after an additional 203 ± 71 days of estradiol treatment. Serum miRNAs were profiled by sequencing. Estrogen status and biomarkers of bone metabolism were quantified. Bone mineral density was assessed in the lumbar spine.ResultsOur analysis revealed 17 miRNAs associated with estrogen levels. Of those miRNAs that were upregulated with estrogen deficiency and downregulated after estrogen therapy, miR-422a correlated with serum beta-carboxy-terminal type I collagen crosslinks (β-CTX) and procollagen 1 N-terminal propeptide (P1NP); and miR-1278 correlated with serum β-CTX, P1NP, osteocalcin, sclerostin, and Dickkopf-1(Dkk1). In contrast, we found an inverse association of miR-24-1-5p with estrogen status and a negative correlation with serum β-CTX, P1NP, osteoprotegerin, and sclerostin levels.ConclusionThe reported miRNAs associated with estrogen status and bone metabolism could be potential biomarkers of bone pathophysiology and would facilitate studies on the prevention of postmenopausal osteoporosis. Our findings require validation in an extended cohort.